What happened in Ecuador in October 2019? - Izurieta , Belén (El Outsider: Journal of International Relations and Political Science, 2020)
For eleven days, the streets of Ecuador were a battlefield. Civilians, police, indigenous and military clashed with each other. The protests began on October 3rd as a result of the dissatisfaction of Ecuadorians with a presidential decree that would nullify fuel subsidies. The protests resulted in violence, repression and vandalism. Throughout those days, Ecuadorians experienced rebel behaviors, lost their individual identity, and showed racist and polarizing feelings. Because of what happened during the protests, this article aims to explain the behavior of Ecuadorians using a psychological perspective.
Keywords: social deindividualization; reactance; perceived injustice; polarization; social mobilization; protests